Well-Being and Ill-Being: A Bivariate Panel Data Analysis - Lee, W; Oguzoglu, U (My University, 2007)
The aim of this paper is to estimate in a multivariate context the factors associated with well-being and ill-being without making the assumptions that they are opposite ends of the same continuum, and that the factors uniformly affect both well-being and ill-being. Using the first five waves of panel data from the Household, Income and Labour Dynamics in Australia (HILDA) survey, we jointly model positive and negative wellbeing in a two-equation dynamic panel data model. We found that while past ill-being had a significant effect on current well-being there was no support for a reverse relationship (i.e. lagged effect of well-being on current ill-being). In addition, we also found support for asymmetry in how certain factors affect well-being and ill-being. The implication of the findings in this paper for the happiness literature is that for future empirical work, it would perhaps more prudent to begin with the notion that well-being and ill-being are distinct dimensions, that the unobservables that affect well-being and ill-being are correlated, and to specify econometric models that allow for these concepts to be reflected.
Melbourne Institute of Applied Economic and Social Research Working Paper Series
Keywords: Health -- Wellbeing; Health; Health and wellbeing; Health